Model of Oxidation‐Induced Fiber Fracture in SiC/SiC Composites. Issue 11 (27th August 2014) - Xu, Wenbo; Zok, Frank W.; McMeeking, Robert M.; Parthasarathy, T.
<x xml:space="preserve">Abstract</x> Stress rupture of SiC/SiC composites at intermediate temperatures in oxidizing environments is the result of a series of internal chemical and thermomechanical processes that lead to premature, localized fiber fracture. This article presents analytical models for two potentially critical steps in this process. The first involves the generation of tensile stresses in the fibers due to SiO2 scale formation (following removal of fiber coatings) and the associated reduction in the applied stress required for fiber fracture. The second occurs once the gaps produced by coating removal are filled with oxide and subsequent oxidation occurs subject to the constraints imposed by the matrix crack faces. In this domain, the failure model is couched in terms of the stress intensification within the fibers caused by constrained oxidation. The models incorporate the combined kinetic effects of oxide growth and viscous flow. The competing effects of increased oxidation rate and accelerated stress relaxation with increasing temperature on fiber stress feature prominently in the results. The results suggest that, in dry air environments, the highest risk of fiber fracture occurs at temperatures in the range 840°C–940°C. In this range, the oxide scales grow at appreciable rates yet the resulting growth stresses cannot be mitigated sufficiently rapidly by viscous flow.